1986
DOI: 10.1085/jgp.87.4.551
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine-induced transport systems in trout erythrocyte. Na+/H+ countertransport or NaCl cotransport?

Abstract: It has previously been shown (Baroin, A,, F . Garcia-Romeu, T . Lamarre, and R . Motais . 1984a, b . Journal of Physiology . 350 :137, 356 :21 ; Mahe, Y ., F . Garcia-Romeu, and R . Motais . 1985 . European Journal of Pharmacology . 116 :199) that the addition of catecholamines to an isotonic suspension of nucleated red blood cells of the rainbow trout first stimulates a cAMPdependent, amiloride-sensitive Na'/H' exchange . This stimulation seems to be transient . It is followed by a more permanent activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 17 publications
(28 reference statements)
6
43
1
Order By: Relevance
“…Cell water content was measured as described as Borgese et al (1986). Briefly, after the incubation period, cells were resuspended at about 30% haematocrit, and poured into nylon tubes which were then centrifuged at 15 000 g for 10 min in a Sorvall refrigerated centrifuge.…”
Section: Methodsmentioning
confidence: 99%
“…Cell water content was measured as described as Borgese et al (1986). Briefly, after the incubation period, cells were resuspended at about 30% haematocrit, and poured into nylon tubes which were then centrifuged at 15 000 g for 10 min in a Sorvall refrigerated centrifuge.…”
Section: Methodsmentioning
confidence: 99%
“…In Necturus gallbladder epithelium18 and in renal brush border vesicles,'9 an increase in cAMP reduces the rate of Na+-H+ exchange and leads to a decrease in pHi, whereas the opposite occurs in trout red blood cells. 20,21 The purpose of this study was to establish 1) the effect of a-and ,3-adrenergic stimulation on pHi of single myocardial cells, 2) whether the changes in pHi that occurred in response to these interventions were Isolation Procedure Ventricular myocytes were enzymatically dissociated with minor modifications of a technique previously described. 22 Briefly, 2-4-month-old male Wistar rats from the Gerontology Research Center Colony were subjected to narcosis with an intraperitoneal injection of sodium pentobarbital.…”
mentioning
confidence: 99%
“…The strong acidification of the medium which occurs at the onset of stimulation has been explained by the fact that part of the Na+ that penetrates the cell is exchanged with H+, which comes from the intracellular buffer, via a Na+-H+ exchange mechanism with a stocheiometry of 1: 1 (Baroin et al 1984b; Cossins & Richardson, 1985). In spite of the fact that NaCl uptake is practically independent of the presence of HCO3-in the external medium and swelling is largely inhibited when Cl-is replaced by N03-, it was suggested that the catecholamine-induced volume increase is mediated by the activation of a Na+-H+ antiport which operates in parallel to a Cl--OH-exchanger, rather than by a NaCl co-transport (Borgese, Garcia-Romeu & Motais, 1986). It should be noted that other systems such as Amphiuma and dog erythrocytes and human blood lymphocytes regulate their volume in response to osmotic shrinkage by the stimulation of a Na+-H+ antiport operating in parallel to a Cl--HC13-exchanger (Cala, 1980(Cala, , 1983bParker, 1983b;Parker & Castranova, 1984;Grinstein, Clarke & Rothstein, 1983;Kregenow, Caryk & Siebens, 1985).…”
mentioning
confidence: 99%